Studi Kasus: Penerimaan Orang Tua dan Altruisme pada Pasangan Suami Istri yang Mengadopsi Anak Berkebutuhan Khusus - Eaglin Gammelia Likumahwa; Rudangta Arianti (Humanitas (Jurnal Psikologi), 2024)
This research aims to describe the dynamics of parental acceptance and altruism in married couples who adopt children with special needs. This research was conducted using a qualitative design with a case study method on a single case. The informant selection technique used was a nonprobability sampling technique, namely purposive sampling. Informants were selected by paying attention to 4 things, namely being a married couple, having an adopted child with special needs with the classification of a child with undiagnosed special needs, having an adoption age of around 8 months and still being cared for and currently not having biological children. Data collection techniques were carried out using observation and in-depth interviews. The examination technique to test the validity of the data in this research was carried out using the credibility test, transferability test, dependability test and confirmability test. The results of this research show that husband and wife couples, in their efforts to build parental acceptance of children with special needs who are adopted, encounter various challenges and difficulties caused by the various limitations of children with special needs. In facing the dynamics of parental acceptance, married couples work together and make various sacrifices to create complete acceptance for children with special needs which is illustrated by achieving 4 aspects of parental acceptance according to Hurlock, namely communication, attention and affection, parental involvement and trust in children. The sacrifice shown is based on the altruistic factors of each partner which Rushton explains into 5 factors, namely feelings, empathy, religiosity, interpersonal relations and social norms.